2019
DOI: 10.1002/ecy.2572
|View full text |Cite
|
Sign up to set email alerts
|

Semiarid ecosystem sensitivity to precipitation extremes: weak evidence for vegetation constraints

Abstract: In semiarid regions, vegetation constraints on plant growth responses to precipitation (PPT) are hypothesized to place an upper limit on net primary productivity (NPP), leading to predictions of future shifts from currently defined linear to saturating NPP–PPT relationships as increases in both dry and wet PPT extremes occur. We experimentally tested this prediction by imposing a replicated gradient of growing season PPT (GSP, n = 11 levels, n = 4 replicates), ranging from the driest to wettest conditions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 45 publications
1
73
1
1
Order By: Relevance
“…More evidence has been found for this integrated model in arid and semi‐arid ecosystems with more positive asymmetry (Haverd, Ahlström, Smith, & Canadell, ; Unger & Jongen, ). However, in our current experiment in the desert steppe, although extreme precipitation levels were included, a linear model was fitted better than nonlinear models for the ANPP and precipitation relationship, which could be attributed to the plant compositional shift and ecosystem resistance/resilience conferred by historical environmental conditions with relative low precipitation (Felton et al, ; Hoover, Knapp, & Smith, ; Knapp et al, ). In a global dryland synthesis, Gherardi and Sala () reported that ANPP responded positively to increased precipitation variability at arid sites with mean annual precipitation below 300 mm, whereas ANPP responded negatively at drylands with mean annual precipitation over 300 mm.…”
Section: Discussionmentioning
confidence: 73%
“…More evidence has been found for this integrated model in arid and semi‐arid ecosystems with more positive asymmetry (Haverd, Ahlström, Smith, & Canadell, ; Unger & Jongen, ). However, in our current experiment in the desert steppe, although extreme precipitation levels were included, a linear model was fitted better than nonlinear models for the ANPP and precipitation relationship, which could be attributed to the plant compositional shift and ecosystem resistance/resilience conferred by historical environmental conditions with relative low precipitation (Felton et al, ; Hoover, Knapp, & Smith, ; Knapp et al, ). In a global dryland synthesis, Gherardi and Sala () reported that ANPP responded positively to increased precipitation variability at arid sites with mean annual precipitation below 300 mm, whereas ANPP responded negatively at drylands with mean annual precipitation over 300 mm.…”
Section: Discussionmentioning
confidence: 73%
“…, Felton et al. ). However, most of these studies focused on aboveground NPP (ANPP), with much less attention given to the hidden belowground portion of NPP, that is, BNPP (Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Felton et al. ). Therefore, using experiments that involve multilevel changing precipitation treatments would more clearly elucidate allocation changes in NPP and the underlying mechanisms, which is critically important for understanding ecosystem functional responses to changing precipitation regimes (McCarthy and Enquist , Bardgett and Wardle ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations